2020 15th IEEE International Conference on Automatic Face and Gesture Recognition (FG 2020) 2020
DOI: 10.1109/fg47880.2020.00110
|View full text |Cite
|
Sign up to set email alerts
|

CLIFER: Continual Learning with Imagination for Facial Expression Recognition

Abstract: Current Facial Expression Recognition (FER) approaches tend to be insensitive to individual differences in expression and interaction contexts. They are unable to adapt to the dynamics of real-world environments where data is only available incrementally, acquired by the system during interactions. In this paper, we propose a novel continual learning framework with imagination for FER (CLIFER) that (i) implements imagination to simulate expression data for particular subjects and integrates it with (ii) a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 33 publications
(61 reference statements)
0
34
0
Order By: Relevance
“…This significantly reduces the number of parameters in the decoder (≈ 2.8M as opposed to 10M in [31]) while also improving the photo-realistic quality of the reconstructed images. The decoder, adapted from the generator model of [5], implements 4 stacked conv layers, using ReLU activation, performing transposed convolutions with 128, 64, 32, 16 filters, respectively, of size (5×5) each with a stride of (2×2). The output of the last conv layer is passed through another transposed conv layer using tanh activation to generate the resultant image (x gen ) with the same dimensions as the FoI (x r ).…”
Section: Decoder For Image Reconstructionmentioning
confidence: 99%
“…This significantly reduces the number of parameters in the decoder (≈ 2.8M as opposed to 10M in [31]) while also improving the photo-realistic quality of the reconstructed images. The decoder, adapted from the generator model of [5], implements 4 stacked conv layers, using ReLU activation, performing transposed convolutions with 128, 64, 32, 16 filters, respectively, of size (5×5) each with a stride of (2×2). The output of the last conv layer is passed through another transposed conv layer using tanh activation to generate the resultant image (x gen ) with the same dimensions as the FoI (x r ).…”
Section: Decoder For Image Reconstructionmentioning
confidence: 99%
“…On the other hand, the emotion recognition module does not need to be constantly modified and is trained only once. While research has shown that personalizing emotion recognition in the context of continual learning increases performance [48,49], the same can be argued for action recognition (personalizing) [50,51]. In this work, we focus on IL in the context of allowing the addition of new classes to the system-personalized adaptation is out of our scope.…”
Section: Methodsmentioning
confidence: 98%
“…Memory-based approaches, on the other hand, store previous experiences in memory and rehearse or indirectly use them in order to avoid forgetting them. To this end, the experiences themselves can be stored ( Robins, 1993 ) or a generative model can be trained to generate pseudo-experiences ( Robins, 1995 ) to rehearse experiences; or an episodic or semantic memory can be learned to retain information for longer terms and to interpret new experiences in the context of such a memory ( Hassabis et al, 2017 ; Churamani and Gunes, 2020 ). Finally, in model-extension approaches, the model (the network architecture) can be extended itself to accommodate the required capacity for the new task or experience ( Draelos et al, 2017 ).…”
Section: Related Workmentioning
confidence: 99%
“…Doğan et al (2018a , b) introduced solutions for addressing lifelong learning of context in robots continually encountering new situations through their lifetimes. As a last example, Churamani and Gunes (2020) proposed a memory-based solution for continual learning of facial expressions that can potentially be used by a humanoid robot to sense and continually learn its user’s affective states.…”
Section: Related Workmentioning
confidence: 99%